When we were very young - Milne, A. A. (Alan Alexander), 1882-1956.; Shepard, Ernest H., (Ernest Howard), 1879-1976 (New York : Puffin Books, 1992)
A collection of poems reflecting the experiences of a little English boy growing up in the early part of the twentieth century.
Corner-of-the-street -- Buckingham Palace -- Happiness -- The christening -- Puppy and I -- Twinkletoes -- The four friends -- Lines and squares -- Brownie -- Independence -- Nursery chairs -- Market Square -- Daffadowndilly -- Water-lilies -- Disobedience -- Spring morning -- The island -- The three foxes -- Politeness -- Jonathan Jo -- At the zoo -- Rice pudding -- Missing -- The King's breakfast -- Hoppity -- At home -- The wrong house -- Summer afternoon -- The dormouse and the doctor -- Shoes and stockings -- Sand-between-the-toes -- Knights and ladies -- Little Bo-Peep and Little Boy Blue -- The mirror -- Halfway down -- The invaders -- Before tea -- Teddy bear -- Bad Sir Brain Botany -- In the fashion -- The alchemist -- Growing up -- If I were king -- Vespers.
Originally published: New York : E.P. Dutton, 1924.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
5.4
3-6
Keywords: Children's poetry, English; English poetry; Children's poetry